Does probation lead to higher starting wage? Evidence from Japanese online job ads - Mirka Zvedelikova (Osaka University, Institute of Social and Economic Research (ISER), 2024)
Firms commonly use probation to evaluate new hires before making long-term commitments. Workers accepting jobs with a high initial risk of dismissal may expect compensation for this risk. Utilizing an original dataset of Japanese online job ads, this study employs propensity score matching and regression analysis to compare wages at the start of employment for jobs without probation and upon probation completion for jobs with probation. The findings reveal no statistically significant difference in starting wages, suggesting that workers are not rewarded for undergoing probation in terms of higher wages at the start of long-term contracts.
Keywords: J31; J41; M5; 330; wage; probation; job ads; Japan